2013
DOI: 10.1007/s10495-013-0944-1
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism by which MEK/ERK regulates JNK and p38 activity in polyamine depleted IEC-6 cells during apoptosis

Abstract: Polyamine-depletion inhibited apoptosis by activating ERK1/2, while, preventing JNK1/2 activation. MKP-1 knockdown by SiRNA increased ERK1/2, JNK1/2, and p38 phosphorylation and apoptosis. Therefore, we predicted that polyamines might regulate MKP1 via MEK/ERK and thereby apoptosis. We examined the role of MEK/ERK in the regulation of MKP1 and JNK, and p38 activities and apoptosis. Inhibition of MKP-1 activity with a pharmacological inhibitor, sanguinarine (SA), increased JNK1/2, p38, and ERK1/2 activities wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Previous studies investigated the crosstalk between ERK and JNK signaling pathways. The ERK activator MEK was reported to regulate JNK activity in rat intestine cell line (IEC-6) and in human astrocyte cell line (U-251) [ 47 , 48 ]. On the other hand, JNK activation was reported to inhibit ERK activation in COS-7 cells and in Bcr/Abl+ human leukemia cells [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigated the crosstalk between ERK and JNK signaling pathways. The ERK activator MEK was reported to regulate JNK activity in rat intestine cell line (IEC-6) and in human astrocyte cell line (U-251) [ 47 , 48 ]. On the other hand, JNK activation was reported to inhibit ERK activation in COS-7 cells and in Bcr/Abl+ human leukemia cells [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…MEK/ERK activity has been reported to regulate JNK activity in apoptotic signaling in IEC-6 cells derived from rat intestine50. In a human astrocyte cell line (U-251), MEK phosphorylated JNK51.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Bavaria et al reported in the apoptosis literature that MEK1/ERK1/2 negatively regulated JNK1/2 phosphorylation via induction of MAP kinase phosphatase-1 (MKP-1). [18] …”
Section: Discussionmentioning
confidence: 99%